Desamparo e melancolia na modernidade: considerações a partir de Virginia Woolf - Vieira, Letícia Lima (2019)
The present work aims to investigate, under the lens of psychoanalysis, melancholy in characters of the book To the lighthouse, by Virginia Woolf. Based on Freudian theory, we reflected about the discontent from the constitution of civilization and the consequent helplessness of the context evidenced in modernity. Faced with the imminence of wars and tragedies, the modern person goes through the process of mourning, which can lead to a melancholy picture. From this context, we used one of the Virginia's diaries and two of her biographies to seek to understand: her creative process and how writing functioned as a sublimation path in the face of frustrations stemming both from her personal circumstances and from the specific unsheltered of modern society. We showed aspects of the melancholy and the feeling of helplessness present in the characters of Virginia and we concluded that the writing played an important role in the maintenance of the writer's life.